2012
DOI: 10.1109/jstsp.2012.2208731
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic Depth Cues Outperform Monocular Ones on Autostereoscopic Display

Abstract: The aim of this study is two-fold; first, to compare how certain visual aids contribute in depth estimation tasks on a portable autostereoscopic display; and second, how these depth cues impact on perceived quality. These were studied on a quantitative subjective study using a portable autostereoscopic display in controlled laboratory environment. Test participants evaluated object depths on three-dimensional images, where either 2D cues, 3D cues, or their combinations were provided. The study was conducted us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 58 publications
(116 reference statements)
0
1
0
Order By: Relevance
“…Contrarily, the objective SIQA method is conducted by computer algorithms, making it an appropriate solution for industries. Basically, such methods are divided into three types: the full reference (FR) [20][21][22][23][24], the reduced reference (RR) [25,26] and the no reference (NR) [27][28][29][30]. In FR-SIQA methods, evaluations are carried out with both the distorted and the original images provided.…”
Section: Previous Work On Siqamentioning
confidence: 99%
“…Contrarily, the objective SIQA method is conducted by computer algorithms, making it an appropriate solution for industries. Basically, such methods are divided into three types: the full reference (FR) [20][21][22][23][24], the reduced reference (RR) [25,26] and the no reference (NR) [27][28][29][30]. In FR-SIQA methods, evaluations are carried out with both the distorted and the original images provided.…”
Section: Previous Work On Siqamentioning
confidence: 99%
“…It was reported that stereoscopic displays did improve the performance of depth-related tasks, such as judging absolute and relative distances, finding and identifying objects, performing spatial manipulations of objects, and spatial navigating (McIntire et al, 2014). However, depth cue interactions should not be neglected (Howard, 2012;Mikkola et al, 2012). For instance, there were interactions among disparity and monocular depth cues, such as motion parallax, occlusion, shadow (or shading), linear perspective, and accommodation ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%